Elimination:
3x - 9y = 3
6x - 3y = -24
3x - 9y = 3
18x - 9y = -72
(subtract)
-15x = 75
÷ -15
x = -5
(3 × -5) - 9y = 3
-15 - 9y = 3
+ 15
-9y = 18
÷ -9
y = -2
Substitution:
6x - 3y = -24
+ 3y
6x = -24 + 3y
÷ 6
x = 4 + 0.5y
3(4 + 0.5y) - 9y = 3
12 + 1.5y - 9y = 3
12 - 7.5y = 3
- 12
-7.5y = -9
÷ -7.5
y = 1.2
x = 4 + (0.5 × 1.2)
x = 4 + 0.6
x = 4.6
So this one didn't fail as much, but I got different numbers. If you have to give in values, I'd give in the values from the elimination because I don't trust myself when it comes to the substitution
(28) 2x+10+x-4=21
(29) 3x-16+4x-8=60
(30) 2x-8+3x-10=17
Answer:
m=7
Step-by-step explanation:
Answer:
b = 24 ft
h = 10 ft
Step-by-step explanation:
120 = ½hb
120 = ½h(3h - 6)
240 = h(3h - 6)
240 = 3h² - 6h
80 = h² - 2h
0 = h² - 2h - 80
0 = (h - 10)(h + 8)
h = 10 ft or -8 ft
we ignore -8 as it makes no sense for a triangle side length.
b = 3(10) - 6 = 24 ft
Answer:
Not equivalent
Step-by-step explanation:
5:3
15:12 simplified = 5:4